The effect of secondary atmospheric parameters on radio wave propagation in a typical Sahel Savannah environment - Akinbolati, Akinsanmi; Abe, Bolanle T. (Edelweiss Applied Science and Technology, 2025)
The need for radio scientists and engineers to consider the atmospheric dynamics of a region is key in the design of communication links. This study was carried out over Katsina City, in the Sahel parts of Nigeria, using mean monthly atmospheric data covering 1980 to 2020. The data were retrieved from the European Centre for Medium-Range Weather Forecast ERA-5 Reanalysis. Refractivity at the surface, 100 m, and 250 m, refractivity gradient (G), and effective earth radius factor (k-factor) were determined using the International Telecommunications Union-Radio Study Group (ITU-R) Recommendation P.453-14, 2019. The data obtained were analyzed, and the results were compared with ITU-R standards. Results indicate higher values of refractivity and k-factor during the wet season compared to the dry season months, meaning there would be more attenuation of radio signals during the wet season compared to the dry season because studies have established a negative correlation coefficient (R) between these parameters and radio signals in Nigeria. Results further indicate a high negative (R) between k-factor and refractivity gradient (G) and a high positive (R) between k-factor and refractivity. The average refractivity for the surface, 100 m, and 250 m were 326.34, 316.39, and 305.07 (N-units) respectively, indicating that radio refractivity decreases with height. The mean k-factor for dry and wet seasons are 1.909 and 2.956 respectively, with an overall mean of 2.433, while the overall mean for (G) is -94.290 (N-units/km). By ITU-R standards, (G) and k-factor results indicate that radio wave propagation would experience a super-refractive effect over the Sahel environment. These results provide valuable applications in the design and reassessment of radio links for terrestrial and satellite communications over the study area or any similar environments in the Sahel region of Africa.